REPRESENTASI IDENTITAS VIRTUAL MAHASISWA PESERTA MBKM MAGANG DALAM AKUN LINKEDIN DI KOTA DENPASAR (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
This study focuses on virtual identity representation in MBKM Internship students in LinkedIn. The puposes of this study is to describe and analyze the virtual identity representation in LinkedIn account of MBKM Internship students. The method used in this study is a quallitative approach. The theory used in analyzing this research is virtual identity theory from Daniel Chandler. The result of this study reveal that the representation of virtual identities in LinkedIn accounts aims to build student virtual identities professionally. The purpose of students using LinkedIn as a means of representing virtual identity is as a means of sharing messages received, a means of increasing job opportunities, media of information about the world of work, interacting with other users, as well as a means of showing the identity of students participating in the MBKM Internship. Efforts made by MBKM Internship participant students to show their virtual identities, namely, completing personal data, completing data in features, being organized in grammar, filling in experience features in work experience, volunteering, and organizations, participating in mini courses, testimonials from other users, and create standalone projects to add to the portfolio. However, regarding LinkedIn, companies are still not active in using LinkedIn, students who are not yet literate about LinkedIn, and people who are not yet integrated with technology make LinkedIn not optimally utilized. Keywords: : LinkedIn, representation, virtual identity, MBKM Magang